'Level up your money game': an analysis of gamification discourse in financial services. Issue 6 (2nd November 2021) - van der Heide, Arjen; Želinský, Dominik
ABSTRACT: The idea of gamification, or implementation of game-like elements and mechanisms in non-game contexts, has, throughout the past decade, swept the fields of healthcare and fitness as well as education. More recently, various tech writers, bloggers, and consultants have begun proposing gamification as a solution also in financial services, where gamification has already made headway, for instance, with day trading apps that simplify trading and turn it into a real-time game. In this paper, we examine the emerging discourse of finance gamification and situate it in the expectational dynamics and performative struggles that shape technological developments in finance and the FinTech industry. We argue that the discourse creates positional uncertainty among finance incumbents by linking the notion of a generational wealth transfer to narratives about generational change. Tech writers, consultants and journalists neutralize this uncertainty by propagating a model of human nature, which may be 'tapped into' and harnessed with games to rationalize subjects' financial behavior. However, despite finance gamification's promises to democratize finance and empower small-time investors by extending access to financial markets, we argue that, in the end, the discourse on finance gamification reinforces the 'observational boundaries' between finance and society.